Fashion as Communication: Costume Dasiyah at Film Series Gadis Kretek - Thessalonica Dwi Setya Angestuti Triantoro; Daniel Budiana; Agusly Irawan Aritonang (Journal of Content and Engagement, 2024)
Film as an audio-visual medium can convey messages verbally and non-verbally. In the filmseries 'Gadis Kretek', the message is communicated through dialogue and visual displays,namely fashion. Dasiyah, as one of the main characters, has iconic fashion compared to othercharacters. Dasiyah Fashion consists of the entire fashion, hair, make-up, and accessories usedby the actress as a costume used as a medium for character communication. Therefore, theauthor is interested in researching the meaning of denotation, connotation, and myths relatedto fashion from each Dasiyah fashion unit using Roland Barthes' semiotic analysis. So thisresearch can find out the full meaning of how fashion can communicate your character. It wasfound that fashion can express Dasiyah's life journey and her ideals regarding kretek amidstthe patriarchy are still strong in Javanese culture. Apart from that, through her fashion, Dasiyahcan position herself in society with her socio-economic status as an elite Javanese woman withher trading activities. The fashion worn by Dasiyah is not always stagnant, there is aprogressiveness of character that causes fashion alterations not by Javanese standards.